Is it possible to evaluate the effectiveness of psychotherapy? - Chaban Олег (Psychosomatic Medicine and General Practice, 2019)
Not so easy. But you can. In general, the evaluative side of psychotherapy in psychiatry has been and remains the most vulnerable place of these sciences and practices. So many people reasonably or unreasonably criticized this method of treatment and correction on its evidence base.